Amplified spontaneous emission from the exciplex state of a conjugated polymer "PFO" in oleic acid. (September 2016) - Idriss, Hajo; Taha, Kamal K.; Aldaghri, O.; Alhathlool, R.; AlSalhi, M.S.; Ibnaouf, K.H.
Abstract: The amplified spontaneous emission (ASE) characteristics of a conjugated polymer poly (9, 9-dioctylfluorenyl-2, 7-diyl) (PFO) in oleic acid have been studied under different concentrations and temperatures. Here, the ASE spectra of PFO in oleic acid have been obtained using a transverse cavity configuration where the conjugated PFO was pumped by laser pulses from the third harmonic of Nd: YAG laser (355 nm). The PFO in oleic acid produces ASE from an exciplex state – a new molecular species. The obtained results were compared with the PFO in benzene. Such ASE spectra from the exciplex state have not been observed for the PFO in benzene. Highlights: Spectral and ASE from conjugated polymers PFO in oleic acid. Effects of oleic acid and ordinary solvents on the spectral and ASE of PFO. Four ASE peaks are attributed from monomeric, dimeric and exciplex states.